Legal Aspect for Teachers in Educating Their Students to Avoid Criminalization - Wulandari, Gendis (NORMA, 2020)
This research, entitled legal aspect for teachers in educating their students to avoid criminalization, aims to find out and analyze how to resolve and prevent disputes for teachers and students so that teachers' actions to students and students to teachers will not be easily criminalized. This is normative legal research that will explore the contents of statutory regulations. Based on the study results, the education system in schools no longer emphasizes academic achievement on paper anymore. Developing and improving students' morality and mentality in social interactions is one crucial element that must be done. One alternative that can be used as a reference for teachers' actions towards their students, mainly the reasons teachers do such acts, is that all Teachers substitute parents in the school.Keywords: Students, Teachers, Criminalization.